Virtual Museum Sebagai Sarana Penyampaian Makna Seni Dan Sejarah Di Masa Pandemi - Putu Aditya Anjasmara Pradipta; Andri Sahata Sitanggang; Muhajirin Muhajirin (UNIVERSITAS RAHARJA, 2022)
The formulation of the problem obtained is a Virtual Museum which can display or visualize objects in the museum and become a medium that provides information about historicalobjects in the museum. In this study we used descriptive-qualitative and phenomenological methods. This study also intends to find out the different adaptations of using virtual technology and the impact on each person's use, because if the impact is good for some people, but can not be generalized as good for all users.This research shows that by providing virtual space, realizing the vision and the mission to hold an art exhibition is not impossible, because there are many resources and technology that we have and can learn from. During this COVID-19 pandemic we are not allowed to travel and visit. With this virtual museum, we hope that art connoisseurs and the public are satisfied and can feel they are in a virtual museum during this pandemic.